Sheep Manure-Tail Vegetable-Corn Straw Co-Composting Improved the Yield and Quality of Mini Chinese Cabbage - Xuehua Wang; Yali Qiao; Jianzhong Tie; Wenbin Zhang; Baihong Wei; Zeci Liu; Jihua Yu; Linli Hu (Foods)
In order to fully utilize the resources of agricultural waste in Gansu Province’s semi-arid area. Local commercial organic fertilizer (ST1) was selected as the control, and four kinds of planting and breeding waste composts (PBCs) were designed with sheep manure (SM), cow manure (CM), tail vegetable (TV), mushroom residue (MR), and corn straw (CS) to study the effects of the different PBC formulations on the yield and quality of mini Chinese cabbage. In contrast to local commercial organic fertilizer, the STS (SM:TV:CS = 6:3:1) treatment increased the economic yield by 5.56%. Additionally, STS also significantly increased the VC content of mini Chinese cabbage, increased the organic acid by 14.66%, increased the free amino acid by 38.98%, and the nitrate concentration was significantly reduced by 41.05%. Meanwhile, the STS formula also increased the concentrations of polyphenols and essential amino acids of mini Chinese cabbage and also had excellent performance in volatile compounds. As a result, the STS formula can make full use of local planting and breeding waste resources and produce high yield and high quality of local mini Chinese cabbage. The study provided a theoretical foundation and technical guidance for screening suitable local compost formulas, as well as for the achievement of high-yield and high-quality mini Chinese cabbage production in the semi-arid areas of central Gansu province.